Municipal Management and Quality of Public Service in Tingo Maria - López López, Alan Dennis (2020)
Objective. To analyze the way in which municipal administration is related to the quality of public service in Provincial Municipality of Tingo Maria, 2019. Methods. The research level was relational, while the non-experimental design was cross-sectional. An opinion questionnaire was applied to know the behavior of the study variables in the users of said municipality. Results. The evaluation of municipal administration yielded a result of 35% "fair", 23% "good", 18% "excellent", 17% "bad" and 8% "lousy". For its part, the quality of the public service yielded a result of 31% "fair", 25% "good", 20% "bad", 14% "terrible" and 11% "excellent". Regarding Pearson's correlation, a value of 0.575 was obtained and the significance of p <= 0.000; demonstrating relationship between municipal administration and the quality of public service. Likewise, the results in the specific hypotheses were: in the first hypothesis, Pearson correlation of 0.488 and the significance of p <= 0.000 were contrasted. In the second hypothesis, a Pearson correlation of 0.542 and a significance of p <= 0.000 were corroborated. Conclusion. There is a significant relationship between municipal administration and the quality of public service in the Provincial Municipality of Leoncio Prado